If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -48 = -3c + 9 Reorder the terms: -48 = 9 + -3c Solving -48 = 9 + -3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3c' to each side of the equation. -48 + 3c = 9 + -3c + 3c Combine like terms: -3c + 3c = 0 -48 + 3c = 9 + 0 -48 + 3c = 9 Add '48' to each side of the equation. -48 + 48 + 3c = 9 + 48 Combine like terms: -48 + 48 = 0 0 + 3c = 9 + 48 3c = 9 + 48 Combine like terms: 9 + 48 = 57 3c = 57 Divide each side by '3'. c = 19 Simplifying c = 19
| 5x-3y-10=0 | | 12-3(5-1)= | | (-4.93)(-2.1)= | | .6y+1=1.4y-15 | | -126=6(-5+2n) | | 4x^2+26x+12=36 | | y+3=20 | | (39-2x)(21-2x)x=equation | | -5.79+3.11y-4.97-2.13y= | | 0.7x-12=-13.75 | | 10x+5=5(1+2x) | | 16+7r-8+7r=8r+5r | | 3(p-3)+7=32-4(2p+5) | | 4.5(x+7)=41.85 | | 34-6x=6-10x | | 4x+11=-49-6x | | (-8+3i)+(-5i)= | | 2+11x=-48+x | | X+12yi=3-6i | | (2x+1)(3-x)=0 | | 3(4x-1.5)-2x=17 | | 8*(x-2)=32 | | 9+4*x=29 | | 315=7(6m+3) | | 12-3*x=3 | | -2x-4=32 | | 7x-17=6x+7 | | (X+6)+x+2x=35 | | .333x-4=2 | | 2*(y^2)-x^2=0 | | -2(12)+12y=47 | | -16x+7=-41 |